Labor relations and “management of human resources” in subsidiaries of multinational companies in Argentina. - Delfini, Marcelo (Sociedad y Economía, 2011)
The Multinational Companies have tended to move to their subsidiaries practices of ‘ human resources management “developed in the native land, resulting in labor relations converging globally and convergent relations worldwide and that modified the labor traditional relations of the countries of installation. The aim of this paper is to investigate to what extent the convergence processes are developed between subsi- diaries of multinational companies in Argentina in the practices of “human resource management” and its impact on labor relations. This analysis was carried out through semi-structured interviews with managers and human resources employees of six mul- tinational firms. The results of this paper show the convergence in the strategies of human resource management “, although with differences in implementation.